Kemampuan Pemahaman Matematis Siswa dengan Menggunakan Cabri 3D - Bayu Jaya Tama; Sri Rezeki; Rezkiyana Hikmah (Journal of Instructional Mathematics, 2020)
The purpose of this study was to determine differences in students' mathematical understanding abilities between those using Cabri 3D by using ordinary learning models. This research is a quasi-experimental research. The sample of the research was grade VIII students of one junior high school in Cibinong. The research instrument used was pretest and posttest. Research data were analyzed using t-test. The results of this study indicate that the mathematical understanding ability of students who learn with 3D cabri media is better than students who study with ordinary learning.